(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2022)
Background: Menstrual hygiene is a matter that is not sufficiently acknowledged. Even though menstruation is a natural phenomena in a woman’s life, it is associated with misconceptions, malpractices and challenges among girls in developing countries. School drop outs are more frequent among girls after they have reached puberty and menstruation is increasingly recognized as a major factor for this. The aim of the study was to assess the situation of menstrual hygiene of adolescent girls in a hilly area of Bangladesh. Materials and methods: This was a cross-sectional study; convenient type of nonprobability sampling technique was applied. The study was performed in Khagrachari Technical School and College and Khagrachari Government Women College among 300 students. Results: Out of 300 adolescent girls studied, the majority was between 16 to 18 years of age. The mean age of menarche in this study subjects was 12.96±1.214 years. Majority (72%) of the adolescents had no idea about menstruation before menarche. One hundred twenty six (42%) girls used sanitary pads during menstruation. In cases of reused cloth, 89 (51.2%) girls dried them outside the house in proper sunlight, 32 (18.4%) girls dried them inside the house hidden under cloths, and 36 (20.6%) girls dried them outside the house but hidden under cloths. Around 264 (88%) girls faced different restrictions during menstruation. Conclusion: Formulating Menstrual Hygiene Management (MHM) programs in the country can have an outcome of great interest. To accomplish this, multiple strategies need to be used such as educational session on reproductive health and menstrual hygiene in schools or by media campaigns. Chatt Maa Shi Hosp Med Coll J; Vol.21 (1); January 2022; Page 47-51